Strengthening the Cultural Identity of Indonesian Children in Malaysia through Education of the Regional Song “Soleram” and the Game “Ampar-Ampar Pisang” - Andri Putraedi; Muhammad Fatahillah; Raissya Hazra Dianies Kurniawati; Citta Puri Indiraloka; Bella Putri Carissa; Desi Destiana Agusman; Siti Nur Azizah; Maudi Rahmawati (Universitas Muhammadiyah Purwokerto, 2025)
This community service activity explores how education through traditional songs and games can help Indonesian diaspora children in Malaysia strengthen their cultural identity. With globalization threatening local identities, diaspora children often struggle to balance their home culture with their new environment. Through observations and interviews with 12 children from grade 5 to junior high school at Sanggar Bimbingan At-Tanzil, this study found that integrating arts and culture into the learning process can deepen children's connection to their heritage. The traditional song